An Exploration of BERT and Its Diverse Applications - Taha, Bewar Neamat; Baykara, Muhammet; Ucar, Ferhat (Ieee, 2025)
This research initially emphasizes the remaining growth of establishing new technologies and methods from science and also technology, which has undoubtedly had a significant impact on a wide range of disciplines as well as numerous sectors, including the manufacturing industry, medicine, health, science, and technology. Then, after that, it presents a detailed investigation of (BERT), its diverse uses and methods from natural language processing (NLP), and its most current breakthroughs, and has significance in a variety of engineering and computer science domains. BERT is based on highly trained deep-learning algorithms. BERT, a cutting-edge pre-trained language model, has grown into a key player in NLP due to its capacity to collect contextual data inside text, enabling advancements in a variety of disciplines. The research also delves into the fundamental structure of BERT and its instruction methods, offering light on its unique ability to recognize bidirectional context inside phrases. Furthermore, this research examines a wide range of applications in which BERT has exhibited significant performance increases. Based on conventional tasks like sentiment analysis, question answering, and named entity recognition to increasingly complicated applications consisting of document summarization, language translation, and conversational AI, BERT demonstrates adaptability throughout a wide range of natural language understanding difficulties and forecasting, producing exceptional outcomes within a wide range of complicated tasks. The research additionally looks into ways to fine-tune and transfer knowledge to adjust BERT to particular domains that are increasing its flexibility. It also discusses BERT's issues and interests from future research avenues from various areas, employing multiple datasets. As a whole, the findings indicate that BERT and its later variations beat standard methods used in DL and ML in the areas of accuracy, speed, and optimal performance when dealing with the most complex problems.
7th International Congress on Human-Computer Interaction, Optimization and Robotic Applications-ICHORA -- MAY 23-24, 2025 -- Ankara, TURKIYE
Keywords: Al; Machine learning (ML); Deep learning (DL); Natural Language Processing (NLP); BERT